Hamstring Activity Before and After Break-Point Angle Calculated By Smartphone Application During the Nordic Hamstring Exercise - Toshiaki Soga; Shota Yamaguchi; Takayuki Inami; Hiromi Saito; Nadaka Hakariya; Naoto Nakaichi; Sho Shinohara; Koki Sasabe; Hayato Nakamura; Teerapat Laddawong; Kei Akiyama; Norikazu Hirose (North American Sports Medicine Institute, 2023)
# INTRODUCTION Previous studies have reported a gradual decrease in biceps femoris (BF) electromyography (EMG) activity after the break-point angle (BPA) during the Nordic hamstring exercise (NHE). However, no investigation has been conducted on BF EMG activity before and after BPA as calculated using a smartphone application (Nordic Angle app). # HYPOTHESIS/PURPOSE The aim of this study was to investigate the BF EMG activity before and after BPA, as calculated using the Nordic Angle app. The hypotheses were that BF EMG activity would peak near the BPA and gradually diminish afterward. # METHODS After a warm-up, participants performed three repetitions of prone leg curls to discern maximum voluntary isometric contraction (MVIC) of the hamstrings. The peak value of the BF EMG activity during the prone leg curl was used to convert BF EMG activity during NHE to %MVIC. BPA during NHE was calculated using the Nordic Angle app by analyzing a movie recorded with an iPhone camera. Additionally, the knee flexion angle during NHE was determined using two-dimensional motion analysis software based on video data. To compare EMG activity before and after BPA calculated by the Nordic Angle app, the knee flexion angle was divided into seven phases: 10-15° before BPA, 5-10° before BPA, BPA ± 5°, 5-10° after BPA, 10-15° after BPA, 15-20° after BPA, and 20-25° after BPA. # RESULTS There was no significant difference between the BPA of the Nordic angle and the knee flexion angle at peak BF EMG activity (d = 0.13, p = 0.678). The BF EMG activity at 20-25° after BPA was significantly lower than the BF EMG activity at BPA ± 5° (d = 0.87, p = 0.011). # CONCLUSIONS To prevent the recurrence of hamstring injuries, it is important to incorporate knee flexion exercises that enhance BF EMG activity at 15-35° of knee flexion (0° indicates a fully extended knee). Thus, it is recommended to keep the BPA of the Nordic Angle within 35° to effectively prevent recurrent hamstring injuries during NHE. # Level of evidence 3b